Capture threshold of bipolar and unipolar pacing of left ventricle via coronary sinus branch: longitudinal study - Stritecky, Jakub; Kremlacek, Jan; Hanus, Josef; Haman, Ludek; Stritecka, Hana; Simka, Jakub; Parizek, Petr (Frontiers in Cardiovascular Medicine, 2023)
Introduction The aim of this paper is to first monitor the changes in the capture threshold of endovascularly placed leads for left ventricle pacing, second to compare the pacing configurations, and third to verify the effect of Steroid elution for endovascular leads. Sample and Method The study included 202 consecutive single centre patients implanted with the Quartet™ lead (St. Jude Medical). The capture threshold and related lead parameters were tested during implantation, on the day of the patient’s discharge, and 3, 9, and 15 months after implantation. The electrical energy corresponding to the threshold values for inducing ventricular contraction was recorded for subgroups of patients with bipolar and pseudo-unipolar pacing vectors and electrodes equipped with and without a slow-eluting steroids. The best setting for the resynchronization effect was generally chosen. Capture threshold was taken as a selection criterion only if there were multiple options with (expected) similar resynchronization effect. Results and Discussion The measurements showed that the ratio of threshold energies of UNI vs. BI was 5× higher (p < 0.001) at implantation. At the end of the follow-up, it dropped to 2.6 (p = 0.012). The steroid effect in BI vectors was caused by a double capture threshold in the NSE group compared to the SE group (p < 0.001), increased by approximately 2.5 times (p < 0.001). The study concludes that after a larger initial increase in the capture threshold, the leads showed a gradual increase in the entire set. As a result, the bipolar threshold energies increase, and the pseudo-unipolar energies decrease. Since bipolar vectors require a significantly lower pacing energy, battery life of the implanted device would improve. When evaluating the steroid elution of bipolar vectors, we observe a significant positive effect of a gradual increase of the threshold energy.